The Nature and Importance of Stimulus Control Deficits in Autistic Children - Rincover, Arnold ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
To assess whether over selectivity is a generalized problem in a given autistic child, eight over selective children were identified and then tested to determine whether they would respond over selectively across a wide variety of tasks. Data suggested that autistic children sometimes respond to multiple features and sometimes they respond over selectively. Preliminary studies also suggested that the relative location of cues strongly influences stimulus control. It was suggested that a training program for autistic children should include a set of target behaviors designed to promote responding to stimuli separated in space. Drawings of stimulus materials and graphs showing response data are included. (SBH)
Sponsoring Agency: North Carolina Univ., Greensboro.
ERIC Note: Paper presented in symposium on "Current Research with Autistic Children" at Association for Behavior Analysis (Dearborn, Michigan, June, 1979).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Attention; Autism; Exceptional Child Research; Responses; Reports, Research; Speeches/Meeting Papers